The Relationship between Emotional Intelligence and Mathematical Competency among Secondary School Students - Nor, Nurul Adibah Khairiyah Mohd; Ismail, Zaleha; Yusof, Yudariah Mohammad (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
Anxiety towards mathematics among secondary school students have been reported. Anxiety creates strong negativeÃ‚Â emotions and can hinder a person's cognitive, learning and academic performance. Fear of mathematics came early inÃ‚Â the educational process and if this is not handled properly, it will negatively affect the students to adulthood. InÃ‚Â learning mathematics, emotional intelligence (EI) impacts on how a person deals with emotions, mathematics and theÃ‚Â general self-regulations strategies that the person adopts. A study was carried out to access secondary studentsÃ¢â‚¬â„¢ EI andÃ‚Â their mathematical competency (MC). The EI was tested using an EI questionnaire for adolescents (IKEM-R/MEQI)Ã‚Â consisting of 7 domains, while the MC was tested using selected questions from PISA (Programme for InternationalÃ‚Â Student Assessment) 2012 released items. Analysis shows that EI predict significantly students MC, but with lowÃ‚Â correlational value. Most of the respondents have moderate level of EI in all 7 domains whereby self awareness andÃ‚Â self-regulation are the two domains with lowest scores. On the other hand, most of the studentsÃ¢â‚¬â„¢ MC are poor. This particular research shows that EI is not a good predictor of MC which contradicts other reports. However it isÃ‚Â suggested that the data collection can be improved by examining studentsÃ¢â‚¬â„¢ EI while they are engaging in activities thatÃ‚Â call for MCs rather than doing it before or after the tasks. Keywords: Emotional Intelligence (EI), emotion, Mathematical Competency (MC), PISA (Programme for International Student Assessment), anxietyÃ‚Â DOI: http://dx.doi.org/10.22342/jme.7.2.3534.91-100